The book of Yokai mysterious creatures of Japanese folklore - Foster, Michael Dylan 1965-; Shinonome, Kijin (Oakland, California University of California Press, 2015)
"Monsters, ghosts, fantastic beings, and supernatural phenomena of all sorts haunt the folklore and popular culture of Japan. Broadly labeled 'yokai,' these creatures come in infinite shapes and sizes, from tengu mountain goblins and kappa water spirits to shape-shifting foxes and long-tongued ceiling-lickers. Currently popular in anime, manga, film, and computer games, many yokai originated in local legends, folktales, and regional ghost stories. Drawing on years of research in Japan, Michael Dylan Foster unpacks the history and cultural context of yokai, tracing their roots, interpreting their meanings, and introducing people who have hunted them through the ages. In this delightful and accessible narrative, readers will explore the roles played by these mysterious beings within Japanese culture and will also learn of their abundance and variety through detailed entries, some with original illustrations, on more than fifty individual creatures. The Book of Yokai provides a lively excursion into Japanese folklore and its ever-expanding influence within global popular culture. It invites readers to examine how people create, transmit, and collect folklore, and how they make sense of the mysteries in the world around them. By exploring yokai as a concept, we can better understand broader processes of tradition, innovation, storytelling, and individual and communal creativity"--Provided by publisher.
Yokai, folklore, and this book -- The language of yokai -- Event becomes object -- Heroes of myth and legend -- Weird tales and weird tastes -- Modern disciplines -- Postwar animation and the yokai boom -- Yokai culture network -- Zone of uncertainty -- The order of yokai -- Wilds -- Water -- Countryside -- Village and city -- Home -- Epilogue.
Includes bibliographical references and index.
Keywords: Yåokai (Japanese folklore)